Clinical Phenotype of De Novo GNAO1 Mutation: Case Report and Review of Literature. Issue 2 (30th April 2015) - Talvik, Inga; Møller, Rikke S.; Vaher, Merilin; Vaher, Ulvi; Larsen, Line HG; Dahl, Hans A.; Ilves, Pilvi; Talvik, Tiina
Mutations in the guanine nucleotide-binding protein (G protein), α activating activity polypeptide O ( GNAO1 ) gene have recently been described in 6 patients with early infantile epileptic encephalopathies. In the present study, we report the phenotype and the clinical course of a 4-year-old female with an epileptic encephalopathy (Ohtahara syndrome) and profound intellectual disability due to a de novo GNAO1 mutation (c.692A>G; p.Tyr231Cys). Ohtahara syndrome is a devastating early infantile epileptic encephalopathy that can be caused by mutations in different genes, now also including GNAO1 . The mutation was found using a targeted next generation sequencing gene panel and demonstrates targeted sequencing as a powerful tool for identifying mutations in genes where only a few de novo mutations have been identified.